G protein coupled receptor 41 regulates fibroblast activation in pulmonary fibrosis via Gαi/o and downstream Smad2/3 and ERK1/2 phosphorylation - Zhengnan Ren; Xiaohua Pan; Jiahong Li; Xiaoliang Dong; Xing Tu; Li-Long Pan; Jia Sun (Elsevier, 2023)
Pulmonary fibrosis is a progressive and fatal fibrotic lung disease with mysterious pathogenesis and limited effective therapies. G protein-coupled receptors (GPRs) participate in a variety of physiologic functions, and several GPRs have critical fibrosis-promoting or -inhibiting roles in pulmonary fibrosis. Here, we explored the role of GPR41 in the pathobiology of pulmonary fibrosis. We found that GPR41 expression was elevated in lung tissues of mice with bleomycin-induced pulmonary fibrosis and lung fibroblasts treated with transforming growth factor-β1 (TGF-β1). Knockout of GPR41 attenuated pulmonary fibrosis in mice, as evidenced by improved lung morphology, decreased lung weight and collagen secretion, and down-regulated α-SMA, collagen type I alpha and fibronectin expression in lungs. Additionally, GPR41 knockout inhibited the differentiation of fibroblasts to myofibroblasts, and decreased myofibroblast migration. By further mechanistic analysis, we demonstrated that GPR41 regulated TGF-β1-induced fibroblast-to-myofibroblast differentiation and Smad2/3 and ERK1/2 phosphorylation via its Gαi/o subunit but not Gβγ subunit. Together, our data indicate that GPR41 is involved in pulmonary fibroblast activation and fibrosis, and GPR41 represents a potential therapeutic target for pulmonary fibrosis.